Pembagian Waris Pra-Kematian Pada Masyarakat Islam Jawa Perspektif Hukum Progresif - Faizurrizqi -AD; Fauzan Zenrif; Zaenul Mahmudi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
The practice of dividing pre-death inheritance in Pehserut Village is an inheritance phenomenon that follows Javanese customary law by prioritizing several aspects of mutual benefit, but the inheritance distribution model that occurs in the Pehserut Village community does not get legality in classical Fiqh or Indonesian positive law. Moreover, the Islamic community in Pehserut Village which incidentally is oriented to the opinion of Sunni scholars on fiqh issues, which distinguishes between the terms grant, will, and inheritance. This article aims to describe the aspects that become the background of the Pehserut village community in carrying out the distribution of the pre-death inheritance of the heirs, as well as understanding the distribution of pre-death inheritance in the Pehserut Village community from the perspective of progressive legal theory. The method used in this paper is a field study, data obtained by interviewing several relevant sources and supplemented with supporting documentation. The results of the study concluded that the distribution process used a method similar to grants and wills, but the Javanese people of Pehserut Village did not call it that but called it the term 'inheritance'.Distribution of Pre-Death Inheritance, Javanese Islamic Community Inheritance, Progressive Law.